Study of factors that influence the awareness to participate in Takaful among Perkeso employees in Kuala Lumpur / Nurin Nazirah Muhammad Kathiran - Muhammad Kathiran, Nurin Nazirah (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
Takaful officially implemented by government on 1985 in Malaysia. Takaful policy holders were only about 11% compared to the insurance industry which is 43%. A study carried out by Hamid & Othman (2009) showed that Muslim consumers do not have adequate understanding and information about the concept and essence of Takaful. This is because, the awareness towards Takaful still lack among people. Thus, the main objectives of this study are to identify whether religious belief, level of knowledge, family and relatives approach and marketing and advertising influence the awareness to participate in Takaful. This study applies quantitative approach with the use of survey questionnaires as the main instrument of data collection. 40 employees of Perkeso in Kuala Lumpur were selected as respondents of this study. Data collected was analysed using descriptive analysis, reliability analysis, correlation analysis and multiple regression analysis to conduct this research. In general, finding of this study shows that the religious belief, level of knowledge, family and relatives approach and marketing and advertising have no significant relationship with the awareness to participate in Takaful.